Development of The Merdeka Curriculum in Educational Units and Implementation of The Merdeka Curriculum in 21st Century Learning - Muhammad Ikhsanuddin; Hanif Hanani; Rizka Setiawan; Kholil; Muhtar Hidayat (UNIVERSITAS SERAMBI MEKKAH, 2024)
The essence of the Merdeka Curriculum is education based on the nature of the environment and the times, where each student has their own talents and interests. The goal of Merdeka Belajar (Freedom to Learn) is to effectively reduce learning delays caused by the Covid-19 pandemic. Although the 2013 Curriculum is still available, schools can prepare themselves to implement the Merdeka Curriculum. Thus, each educational unit can decide the right time to start implementing and applying the new curriculum independently according to their readiness. The idea of the essence of Merdeka Belajar is to create a joyful learning atmosphere without the burden of achieving specific grades (Sudaryanto et al., 2020). Therefore, before schools implement the new curriculum, an analysis needs to be conducted to take active steps. By taking these steps, it is expected that schools can better understand the Merdeka Curriculum, from preparation and implementation to the evaluation of the learning process. This will greatly assist in accelerating the development of the Merdeka Curriculum according to KKNI in these schools.